Analisis Motivasi Belajar Siswa Kelas V SDN Cibabat Mandiri 2 pada Materi Sudut dalam Mata Pelajaran Matematika dengan Bantuan Media Polypad - Ismi Amelia; Indah Dahlia; Etrin Rhut Nugraheni; Ratna Sariningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
his study aims to determine the learning motivation of grade V students in angular material in the subject of Mathematics with the help of Polypad media. The research method used in this study is a descriptive method with a quantitative approach and data analysis using Microsoft Excel software. The sample used in this study was 30 students in grade V of SDN Cibabat Mandiri 2. The instrument used was in the form of a questionnaire consisting of 5 indicators that included 15 questions, consisting of 8 positive questions and 7 negative questions. The results showed that the use of Polypad media significantly increased students' motivation to learn, with an average motivation percentage reaching 78%, which was in the "Good" category. These results show that Polypad media is able to create more interactive and interesting learning, so that it can increase student motivation and involvement in learning mathematics.